An efficient data evacuation strategy for sensor networks in postdisaster applications - Liu, Ming (2013)
Disasters often result in a tremendous cost to our society. Previously, wireless sensor networks have been proposed to provide information for decision making in postdisaster relief operations. The existing WSN solutions for postdisaster operations normally assume that the deployed sensor network can tolerate the damage caused by disasters and maintain its connectivity and coverage, even though a significant portion of nodes have been physically destroyed. Inspired by the “blackbox” technique, we propose that preserving “the last snapshot” of the whole network and transferring those data to a safe zone would be the most logical approach to provide necessary information for rescuing lives and control damages. In this paper, we introduce data evacuation (DE), an original idea that takes advantage of the survival time of the WSN, that is, the gap from the time when the disaster hits and the time when the WSN is paralyzed, to transmit critical data to sensor nodes in the safe zone. Numerical investigations reveal the effectiveness of our proposed DE algorithm.